Reconstructive and aesthetic genital surgery - Zeplin, Philip H. (Thieme, 2020)
"Your expert introduction to genital surgery techniques This unique work describes the possibilities and limitations of modern reconstructive and aesthetic surgery of the female and male genitalia. Reconstruction of congenital and acquired abnormalities or defects - both functional and aesthetic - is a major challenge, as is individualized treatment in the case of diagnostically verified transsexualism. Surgical procedures in this highly sensitive body region require unusually detailed knowledge of the anatomy and a well-founded operative training, which goes beyond specialist training. Written by a panel of European experts in genital surgery, the work successfully links the fields of plastic surgery, gynecology, urology, and dermatology"--Publisher's description.